Therapeutic potential of green synthesized silver nanoparticles loaded PVA hydrogel patches for wound healing - Ahsan, Anam; Farooq, Muhammad Asim (Journal of drug delivery science and technology, 2019)
Silver nanoparticles were synthesized from cabbage (Brassica oleracia capitate) extract following green chemistry approach and characterized by UV–Vis spectroscopy, DLS, SEM and FT-IR. Furthermore, PVA hydrogel patches loaded with these green synthesized AgNPs and AgNP/clay/activated carbon biocomposites were designed and developed by Freeze-thaw method and their characterization was done by FT-IR and SEM. Swelling studies for these hydrogel patches were performed and overall thickness of these hydrogel patches lied between 0.34 and 0.36 mm. Antibacterial activity of hydrogel patches (10% aqueous soln.) was checked against two representative bacterial strains (Staphylococcus aureus and Escherichia coli) using microdilution method. The minimum inhibitory concentration (MIC) of AgNP-HP and AgNP-Bc-HP for Staphylococcus aureus was 25 μg/mL and 12.5 μg/mL respectively whereas for Escherichia coli it was 3.13 μg/mL and 6.3 μg/mL respectively. Wound healing study was carried out using rabbits as experimental models after giving wound incision on the dorsal skin of these rabbits. Wounds were grossly observed for wound healing over a period of 20 days after application of hydrogel patches on regular basis. Wound healing score was recorded after every 5 days and skin biopsies were taken at 2nd and 3rd weeks of study for histopathological examination. These PVA hydrogel patches proved to be an excellent candidate for wound healing. [Display omitted]